Management of Postoperative Neurosurgical Patients - Panda, Nidhi B.; Mahajan, Shalvi; Chauhan, Rajeev (Journal of Neuroanaesthesiology and Critical Care, 2019)
Neurosurgical patients are a special subset of patients requiring postoperative care. Challenging neurosurgical disease processes, advanced surgical techniques, and unique individual patient requirements advocate the need for meticulous postoperative care to ensure safe transition toward recovery. Timely detection of systemic and neurological changes allows early diagnostic and therapeutic interventions. The mainstay of postoperative care revolves around airway, maintenance of hemodynamics, sedation, analgesia, nutrition, fluid management, and management of disease-specific complications. In addition to standard monitoring, multimodal neuromonitoring should be used in neurosurgical patients. Hence, four key elements in the postoperative management of neurosurgical patients involve profound insight, rapid response, good communication skills, and team collaboration.
Keywords: neurocritical care; aneurysmal subarachnoid hemorrhage; traumatic brain injury; neurosurgery